When Watching Video, Many Saccades Are Curved and Deviate From a Velocity Profile Model - Costela, Francisco M.; Woods, Russell L. (Frontiers in Neuroscience, 2019)
Commonly, saccades are thought to be a ballistic eye movement, not modified during flight, with a straight path and a well-described velocity profile, even though saccade curvature has been reported previously. In a prior study, we developed a real-time, saccade-trajectory prediction algorithm to improve the updating of gaze-contingent displays. We found that saccades with a curved path or that deviated from the expected velocity profile were not well fit by our saccade-prediction algorithm, and thus had larger updating errors than saccades that had a straight path and a conventional velocity profile. Further, we felt that the curved and non-conventional velocity-profile saccades were more common than we had expected when participants performed a natural-viewing task. Since those saccades caused larger display updating errors, we sought a better understanding of them. Here we examine factors that could affect curvature and velocity profile of saccades using a pool of 218,744 saccades from 74 participants watching ‘Hollywood’ video clips. Those factors included characteristics of the participants (e.g. age), of the videos (importance of faces for following the story, genre), of the saccade (e.g. magnitude, direction), time during the session (e.g. fatigue) and presence and timing of scene cuts. While viewing the video clips, saccades were most likely horizontal or vertical over obliques. Measured curvature and velocity-profile error had continuous, skewed frequency distributions. We used mixed-effects multiple regression models that included restricted cubic spline fits and found a complex relationship between curvature, velocity-profile error and saccade duration (or magnitude). Curvature and velocity-profile error were related to some video-dependent features such as lighting, face presence, or nature and human figure content, but there were no effects of subject factors such as age or gender. Time during the session was a predictor for saccadic curvatures. Saccades characteristics vary with a variety of factors, which suggests complex interactions between oculomotor control and scene content that could be explored further.